2016
DOI: 10.12659/msm.898271
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Acute Peritoneal Dialysis in Critically Ill Newborns

Abstract: BackgroundTo evaluate the efficacy, complications, and mortality rate of acute peritoneal dialysis (APD) in critically ill newborns.Material/MethodsThe study included 31 newborns treated in our center between May 2012 and December 2014.ResultsThe mean birth weight, duration of peritoneal dialysis, and gestational age of the patients were determined as 2155.2±032.2 g (580–3900 g), 4 days (1–20 days), and 34 weeks (24–40 weeks), respectively. The main reasons for APD were sepsis (35.5%), postoperative cardiac su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 24 publications
2
24
0
1
Order By: Relevance
“…In a study by Blowey et al 24 conducted on 23 newborn infants who underwent PD, the mortality rate was reported as 35%. Studies carried out in different regions of Turkey by Hakan et al, 16 Alparslan et al 25 and Ustyol et al, 26 reported mortality rates of 74%, 59.3% and 54.8%, respectively. Other studies reported mortality rates of 69%e80% in preterm newborns with AKI.…”
Section: Discussionmentioning
confidence: 97%
“…In a study by Blowey et al 24 conducted on 23 newborn infants who underwent PD, the mortality rate was reported as 35%. Studies carried out in different regions of Turkey by Hakan et al, 16 Alparslan et al 25 and Ustyol et al, 26 reported mortality rates of 74%, 59.3% and 54.8%, respectively. Other studies reported mortality rates of 69%e80% in preterm newborns with AKI.…”
Section: Discussionmentioning
confidence: 97%
“…Utysol et al described the successful application of PD to extremely low-birth-weight infants (weighing as low as 580 g). 11 Because of the lack of successful strategies for preventing or treating AKI, the primary therapy for severe cases of AKI is RRT. Indications for RRT in neonates include refractory acidosis, uremia, electrolyte abnormalities, and fluid overload, as well as inability to provide adequate nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…In a study describing the use of acute PD in critically ill newborns, Utysol et al found that the overall mortality rate was 54.8% and could be as much as 81.3% in premature neonates. 11 Regarding CRRT, a report from the Prospective Pediatric Continuous Renal Replacement Therapy Registry showed that the mortality rate was 57% among infants weighing no more than 10 kg and 36% among infants weighing more than 10 kg. 25 Lee and Cho also reported a mortality rate of 50% in 34 neonates who received CRRT for AKI.…”
Section: Discussionmentioning
confidence: 99%
“…While haemodialysis is the most effective measure for treating hyperammonemia, this is not usually feasible, therefore peritoneal dialysis is commonly done in neonates and young infants [9,10]. Institution of prompt and appropriate treatment before the confirmation of a diagnosis may be life-saving and will reduce the neurological sequelae [11].…”
Section: Discussionmentioning
confidence: 99%